2011
DOI: 10.1088/2040-8978/14/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the extreme scattering effect for particles inside and above a noble metal film via the discrete sources method

Abstract: In this paper the discrete sources method is applied to analyze the extreme scattering effect for particles located both inside and on a gold film deposited on a glass prism. The extreme scattering effect is an effect of the sharp increase of the scattered intensity for P-polarized excitation which occurs in the evanescent wave region behind the critical angle. Moreover, the intensity enhancement appears not only in the transmission direction but in the backscattering direction as well. The effect does not dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The overall reflected light detected by the camera (I) is given by [44][45][46][47][48][49][50][51][52] ,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall reflected light detected by the camera (I) is given by [44][45][46][47][48][49][50][51][52] ,…”
Section: Methodsmentioning
confidence: 99%
“…One reason for this difference is that evanescent wave scattering can greatly enhance the scattering cross section. It has been reported that over three orders of magnitude scattering cross section enhancement for nanoparticles in evanescent field generated by p-polarized excitation 52,53 . It is possible that other less understood effects also contribute to the scattering cross section enhancement given that the surface condition is more complex than that in iSCAT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, the interaction of a P-or S-polarized plane wave (λ = 670 nm) with a AuNP (52 nm in diameter) deposited above a multilayered structure, composed of a Au film (thicknesses of 53 and 46 nm) deposited on a LASF46A prism, has been simulated by using the discrete source method (DSM). 49 The simulated system considered the upper half-space filled with air. The critical angle at which evanescent waves were generated was calculated to be 31.52°.…”
mentioning
confidence: 99%
“…DDA, instead, describes the NP as an array of polarizable dipolar elements organized on a lattice. Only recently, the interaction of a P- or S-polarized plane wave (λ = 670 nm) with a AuNP (52 nm in diameter) deposited above a multilayered structure, composed of a Au film (thicknesses of 53 and 46 nm) deposited on a LASF46A prism, has been simulated by using the discrete source method (DSM) . The simulated system considered the upper half-space filled with air.…”
mentioning
confidence: 99%